Social Capital and Fear of Crime in Adolescence: A Multilevel Study. Issue 1 (19th July 2016) - Vieno, Alessio; Lenzi, Michela; Roccato, Michele; Russo, Silvia; Monaci, Maria Grazia; Scacchi, Luca
Abstract: Hierarchical linear modeling was used to examine the relationships between social capital (at the individual, the neighborhood, and the regional levels) and adolescents' fear of crime, while controlling for the main individual (sociodemographics, television viewing, and bullying victimization), neighborhood (neighborhood size and aggregated victimization), and regional (crime rate and level of urbanization) variables. Data were analyzed using a three‐level model based on 22, 639 15.7‐year‐old ( SD  = 0.67) students nested within 1081 neighborhoods and 19 Italian regions. The findings revealed that individual and contextual measures of social capital, modeled at the individual, neighborhood, and regional levels simultaneously, showed negative associations with adolescents' fear of crime. Males and participants with higher family affluence were less likely to feel fear of crime, whereas victimization, both at the individual and neighborhood levels, had a positive association with fear of crime. Strengths, limitations, and potential applications of the study are discussed.